Spesimen Capung (Odonata) Koleksi Kebun Raya Bogor: Proses Pembuatan dan Identifikasi - Rachmatiyah, Rina; Pungki Lupiyaningdyah (LPPM Universitas Terbuka, 2023)
Dragonfly (Odonata) specimens that have been collected for 76 years (1929-2005) by the Bogor Botanical Gardens (BBG) and kept at the Zoologicum Bogoriense Museum (ZBM) are interesting to study because quite a number of these specimens have not been identified at the species taxon level. The research objective was to record and identify dragonfly species that once lived and were found flying in the BBG area and have become ZBM specimen collections. The research method used is by sorting, grouping, and identifying specimen collections. The identification results of dragonfly specimen collection showed that there were 1,357 specimens consisting of 7 families and 25 species. The most collected family was Libellulidae. The most collected species was Agriocnemis femina (311 specimens), followed by Crocothemis servilia (245 specimens), and Brachythemis contaminata (217 specimens). The year 1995 was the year with the highest number of specimens collected at 1,137 specimens. Garuda Park Pond, Building 9 Pond, Palace Pond, and inside the botanical garden area were the locations with the most dragonfly encounters.